2019
DOI: 10.22603/ssrr.2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Clinical Results of Microendoscopic Decompression for Lumbar Foraminal Stenosis

Abstract: Introduction There have been several reports on surgical techniques involving microendoscopy or percutaneous endoscopy for treating lumbar foraminal stenosis (LFS). However, no studies have assessed the mid-term clinical results of endoscopic techniques in spite of their relatively long history. In this study, we report 20 consecutive cases of LFS treated by our microendoscopic technique focusing on clinical results with a follow-up of at least two years. Methods Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The titles and abstracts of the remaining 561 references were screened, and 506 were excluded because they did not meet the inclusion criteria. The remaining 55 articles underwent full-text screening, of which a further 28 articles were excluded because 17 ( 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ) were on patients with foraminal stenosis and an excluded indication, 4 ( 26 , 27 , 28 , 29 ) were on open decompression, 3 ( 30 , 31 , 32 ) reported no outcomes of interest, 2 ( 33 , 34 ) were letters to editors or surgical technique notes, 1 ( 35 ) was on foraminal stenosis secondary to fusion surgery, and 1 ( 36 ) was on a combination of 2 or more procedures. A further four articles were excluded because one ( 37 ) was on a subset of a larger cohort ( 38 ), and three ( 39 , 40 , 41 ) presented the outcomes of interest graphically or as net changes but did not present specific postoperative values (the authors were contacted at least three times but none responded).…”
Section: Resultsmentioning
confidence: 99%
“…The titles and abstracts of the remaining 561 references were screened, and 506 were excluded because they did not meet the inclusion criteria. The remaining 55 articles underwent full-text screening, of which a further 28 articles were excluded because 17 ( 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ) were on patients with foraminal stenosis and an excluded indication, 4 ( 26 , 27 , 28 , 29 ) were on open decompression, 3 ( 30 , 31 , 32 ) reported no outcomes of interest, 2 ( 33 , 34 ) were letters to editors or surgical technique notes, 1 ( 35 ) was on foraminal stenosis secondary to fusion surgery, and 1 ( 36 ) was on a combination of 2 or more procedures. A further four articles were excluded because one ( 37 ) was on a subset of a larger cohort ( 38 ), and three ( 39 , 40 , 41 ) presented the outcomes of interest graphically or as net changes but did not present specific postoperative values (the authors were contacted at least three times but none responded).…”
Section: Resultsmentioning
confidence: 99%
“…Ahn et al [4] described a PELF and reported that 91% of the patients achieved good or excellent outcomes using the Oswestry disability index. Yoshimoto et al [13] also reported that foraminal decompression alone had good outcomes, potentially eliminating the need for fusion surgery. Although the present study demonstrated that operation time per neuroforamen and intraoperative blood loss showed no significant difference between the 2 groups, the percutaneous endoscopic technique preserves the muscles and spinal structures, with patients of this technique recovering faster than those who undergo surgery using the conventional techniques [14].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the nerve root is easier in the medial part than in the lateral part of the surgical field because the nerve root runs anteriorly in the lateral part. Additional resection of the caudal part of the upper pedicle is necessary for patients with up-down stenosis ( Figure 5 b), and resection of the ligamentum flavum and/or cranial part of the superior articular process of the lower vertebra may be necessary for those with front-back stenosis at the foramen [ 25 ]. However, a biomechanical study revealed that, to prevent postoperative instability, no more than 50% of the lateral part of the facet and/or pars interarticularis should be removed [ 26 ].…”
Section: Surgical Technique For Foraminal Stenosismentioning
confidence: 99%
“…Revision surgery was required in two cases (6.3%) because of residual stenosis in the foramen. Yoshimoto et al [ 25 ] reported midterm clinical outcomes, with an average follow-up of 66.3 months. Their reports included two cases each of L4/5 and L5/6 foraminal stenosis in addition to 16 cases of L5/S1 foraminal stenosis, and the mean recovery rate of the JOA score was 63.9% at the final follow-up.…”
Section: Clinical Outcomes Of Microendoscopic Lumbar Decompressionmentioning
confidence: 99%